Nietzsche's economy : modernity, normativity and futurity - Sedgwick, Peter R. (Palgrave Macmillan, 2007)
This book offers an interpretation of Nietzsche's writings that situates them in relation to the notions of modernity and the sphere of economic and industrial culture. Nietzsche is revealed to be a thinker who is inescapably bound up with his times: economically inspired notions of exchange, credit, debit, sacrifice, labour, posession, expenditure, surplus, measuring, weighing, evaluating, and the like permeate his thought. Starting with the Untimely Meditations, ths study charts Nietzsche's early critical interest and engagement with the realm of commercial culture, his later criticisms of the cultural domination of modern mercantilism (in such works as Human, All Too Human, Daybreak, and The Gay Science) and his mature development of an account of modern society as an amalgam of contemporary practices residing upon ancient economically derived foundations. These elements are related to Nietzsche's vision of the overman and his conception of philosophy as a legislative enterprise.